A Novel Fluoroscopic Approach to Assessing Patient Positioning in Total Hip Arthroplasty: Accuracy and the Influence of Body Mass Index. Issue 6 (10th November 2016) - Lambers, Anton P.; Jennings, Robert; Bucknill, Andrew T.
Introduction: Accurate prosthetic cup placement is important in total hip arthroplasty (THA) and can be influenced by patient positioning. This study aims to assess the accuracy of patient positioning prior to THA, describe a new technique of assessment, and evaluate the influence of body mass index (BMI) on positioning error. Methods: A consecutive series of 37 patients undergoing unilateral THA were investigated. After patient positioning in lateral decubitus, a lateral fluoroscopic image through the table was taken. The C-arm of the image intensifier was manipulated in 2 planes (coronal, transverse) until a perfect lateral view of the pelvis was obtained, defined as when the native acetabulae were superimposed. Degrees of positioning error in the 2 planes were recorded, along with patient BMI. Results: There were 6 patients (16%) positioned within 2° of true lateral in both planes. A further 21 patients (57%) had an error of 5° or more in at least 1 plane. Mean absolute positioning error was 3.0° (SD 2.2°; range 0°-9°) and 3.0° (SD 3.2°; range 0°-13°) in the transverse and coronal planes respectively. Pelvic adduction in the coronal plane was 4.5 fold more likely than abduction (49% vs. 11%). Correlation was shown between patient BMI and the combined error in the 2 planes (R = 0.48, p = 0.001). Discussion: Fluoroscopic positioning assessment prior to THA demonstrates that significant malpositioning is common and more likely with increasing BMI. This technique may be particularly useful for patients with a BMI of >30 kg m-2.